Diferencias de los motores de desarrollo de videojuegos como Unity o Unreal Engine, para el desarrollo de videojuegos para el Sistema Operativo Android - Chavez Rodríguez, Joselo Alexander (2021)
The objective of this case study is to determine the differences that exist between the two best-known video game engines in the world, such as Unity and Unreal. For this, a descriptive and documentary methodology was used with an observation research technique. In addition, the work has an observation table, which had the application of all the aspects found as a programming mode or a way to export the video game among others, in turn it was possible to determine what are the differences that exist between both engines for the video game development on the Android operating system. As a result, it was possible to obtain the main differences that exist between the most popular video game development engines in the industry, which are between Unity and Unreal.